204k views
5 votes
-5mn + 6n - 4m + 2mn + 8n + 3m simplify please show your work

2 Answers

2 votes

Answer:

−3mn−m+14n

Explanation:

(−5m)(n)+6n−4m+2mn+8n+3m

=−5mn+6n+−4m+2mn+8n+3m

Combine Like Terms:

=−5mn+6n+−4m+2mn+8n+3m

=(−5mn+2mn)+(−4m+3m)+(6n+8n)

=−3mn+−m+14n

Answer:

=−3mn−m+14n

User FTM
by
4.7k points
4 votes

Answer:

-3mn + 14n - m is your answer.

Explanation:

Combine like terms (terms with the same amount of variables). Reorder so that it is so:

(-5mn + 2mn) + (6n + 8n) + (-4m + 3m)

Combine like terms. Add or subtract the variables. Note that if there is no number, it is assumed that there is a 1:

(-5mn + 2mn) = (2mn - 5mn) = -3mn

(6n + 8n) = 14n

(-4m + 3m) = 3m - 4m = -m

(-3mn) + (14n) + (-m)

-3mn + 14n - m is your answer.

~

User Mlegg
by
4.7k points